The Impact of Using Social Networking Sites on the Level of Academic Procrastination Among University Students - Aljarrah, Fatima Nasser; Khasawneh, Hala yousef; alFwaeer, HeyamYousef (Journal of Posthumanism, 2025)
The current study evaluates how university students use social networking sites (SNS) to procrastinate academic tasks by examining their connection between psychological variables and SNS usage behavior. A random survey of 350 university students from various disciplines was the basis for the quantitative research design, which used survey data collection. A structured survey containing demographic data and modified Procrastination Assessment Scale for Students (PASS) assessments, and patterns of social networking service usage, measured student procrastination levels. SPSS software analyzed the data through descriptive statistics, Pearson correlation analysis,d, multiple regressio,n and ANOVA as statistical techniques. According to the results, academic procrastination demonstrated a strong positive relationship with daily social networking site utilization (r = 0.53, p < 0.001). Students using SNS frequently showed more procrastination behavior. Among the predictors which impact procrastination behavior, SNS addiction demonstrated the strongest effect (β = 0.61, p < 0.001), while daily SNS use habit (β = 0.46, p < 0.001) and distraction levels (β = 0.43, p < 0.001) and preference for immediate rewards were ranked as next most influential (β = 0.39, p < 0.001). The users on TikTok reported the most platform-based procrastination (M = 4.6, SD = 0.9), and Instagram users followed closely with M = 4.4 (SD = 0.8), while WhatsApp users demonstrated the least procrastination (M = 3.3, SD = 1.2). A significant difference between students’ procrastination and their SNS addiction levels was found according to ANOVA statistics (F = 9.33, p < 0.001). Highly addicted students displayed the most procrastination (M = 4.6, SD = 0.7) when compared to students with moderate (M = 3.8, SD = 0.9) and low addiction (M = 2.9, SD = 0.8). Study productivity suffers from excessive social network site usage, so researchers highlight the need for intervention techniques that assist students to handle their SNS use and fight procrastination behavior. State officials, along with educational institutions, should emphasize time management research with self-regulation training and public awareness programs to minimize study-related risks from using social networking sites excessively.